The Effect of Perceived Ease of Use on User Satisfaction in Applications Mobile Legend in Bandung with Demography as A Moderating - Riska Apriliani; Arry Widodo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The rapid development of technology has made technological developments also create new perspectives in society. One of them is games . Currently, games have become one of the competitions. Mobile Legend is the most played game but has a lower rating on the App Store and Play Store than its competitors. According to user reviews, one of them is an application that often exits on its own. This shows that there are difficulties in using the application, if this continues it will affect the satisfaction of Mobile Legend users. According to previous research, it also shows that demographics strengthen satisfaction. This research was conducted to determine the effect of perceived ease of use on the satisfaction of Mobile Legend users in Bandung with demography as a moderating variable. The research method used in this study is a quantitative method with Structural Equation Modeling (SEM) analysis techniques using SMART PLS software. The sampling method used is purposive sampling with the number of respondents 385 people. The results showed that Perceived Ease of Use had a positive and significant effect on User Satisfaction. With a value of 81.5% as a forming factor for User Satisfaction and the remaining 18.5% is another factor that does not exist in this study. Gender, occupation and income moderate the effect of perceived ease of use on user satisfaction. Meanwhile, gender does not moderate the relationship between perceived ease of use and user satisfaction.